Konsep Ihya`ul mawat Dalam Perspektif Hukum Islam dan Relevansinya Terhadap Hukum Pertanahan di Indonesia - Putri Junita; Filzah Auliya (SALSABIL : Jurnal Syariah dan Hukum Ekonomi, 2025)
This article discusses the concept of Ihya`ul mawat in the context of land law in Indonesia, focusing on the control and management of land that is not owned by anyone. Ihya`ul mawat is a concept that holds deep meaning in Islamic tradition, referring to a person's effort to revive unproductive land or fields in a legitimate manner and in accordance with religious principles. After the agrarian law was enacted in 1960, the land law system in Indonesia underwent significant changes, eliminating dualism and integrating various land rights. This research aims to examine the application of ihya`ul mawat in human life to avoid misunderstandings in interpreting ihya`ul mawat and its implementation, and to understand the differences between the concept of ihya` ul-mawat in fiqh and land tenure in Indonesia. The results of this study indicate that there are differences between the concept of ihya` ul-mawat in fiqh and land tenure in Indonesia, as well as principles of good and just land management. Additionally, it aims to help distribute more perceptions and knowledge about the relevance of the concept of ihya`ul mawat in life and provide practical recommendations to enhance the effectiveness of life. The research method used is a qualitative approach based on library research of relevant documents and literature. discuss various aspects of Islamic law related to the utilization of dead land.